2018
DOI: 10.1136/bmjsem-2017-000305
|View full text |Cite|
|
Sign up to set email alerts
|

Does ovulation affect performance in tennis players?

Abstract: BackgroundScientific data on the performance of collegiate female tennis players during the menstrual phases are scarce.Trial designDouble-blind, counter-balanced, crossover trials were conducted to examine whether tennis performance was affected during menstruation, with and without dehydroepiandrosterone sulfate (DHEA-S) supplementation.MethodsTen Division 1 collegiate tennis players (aged 18–22 years) were evenly assigned into placebo-supplemented and DHEA-supplemented (25 mg/day) trials. Treatments were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
2
8
0
1
Order By: Relevance
“…The initial meta-analysis comprised pooling of pairwise effect sizes comparing exercise performance during the early follicular phase of the MC with all other MC phases (late follicular, ovulation, early luteal, mid-luteal and late luteal). From the 78 studies that were eligible for the systematic review, 51 studies [ 19 , 27 29 , 31 , 34 37 , 54 60 , 62 67 , 70 72 , 74 , 75 , 77 , 78 , 81 , 84 – 86 , 89 94 , 96 , 99 , 101 103 , 105 – 107 , 109 , 114 – 116 ] included assessment of exercise performance during the early follicular phase of the MC and included all other data required for calculations. The 51 studies (mode quality rating = “low”; 8% “high”; 24% “moderate”; 37% “low”; 31% “very low”) generated 362 pairwise effect sizes (240 strength and 122 endurance) with an average of four outcomes per study and a range from 1 to 12 outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The initial meta-analysis comprised pooling of pairwise effect sizes comparing exercise performance during the early follicular phase of the MC with all other MC phases (late follicular, ovulation, early luteal, mid-luteal and late luteal). From the 78 studies that were eligible for the systematic review, 51 studies [ 19 , 27 29 , 31 , 34 37 , 54 60 , 62 67 , 70 72 , 74 , 75 , 77 , 78 , 81 , 84 – 86 , 89 94 , 96 , 99 , 101 103 , 105 – 107 , 109 , 114 – 116 ] included assessment of exercise performance during the early follicular phase of the MC and included all other data required for calculations. The 51 studies (mode quality rating = “low”; 8% “high”; 24% “moderate”; 37% “low”; 31% “very low”) generated 362 pairwise effect sizes (240 strength and 122 endurance) with an average of four outcomes per study and a range from 1 to 12 outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Authors have found similarly mixed results, independently of the tested task or athlete level [ 18 , 19 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 ]. No variation in jumping or sprinting abilities across MC was reported [ 18 , 19 ], but in tennis, it should be noted that, although the speed of the serve did not vary, its accuracy decreased in PeO [ 212 ].…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…Authors have found similarly mixed results, independently of the tested task or athlete level [ 18 , 19 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 ]. No variation in jumping or sprinting abilities across MC was reported [ 18 , 19 ], but in tennis, it should be noted that, although the speed of the serve did not vary, its accuracy decreased in PeO [ 212 ]. Many parts of the body implicated in motor control are known to be impacted by sex hormone variations, but whether the sum of those mechanisms is detrimental to the production of motor tasks remains unknown.…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…Compared to anaerobic and aerobic performance, muscular strength seems more likely to be affected by MC phase. Muscular strength, determined by tests measuring maximal voluntary contractions and force production, was reported in five studies as being affected by MC phase [ 21 , 68 , 91 , 101 , 103 ], whilst five studies reported no MC phase effects on strength [ 52 , 71 , 94 , 95 , 99 ] and one study reported a change in some strength outcomes and no change in other strength outcomes [ 89 ].…”
Section: The Impact Of Menstrual Cycle Phase On Objectively Measurmentioning
confidence: 99%
“…However, multiple studies presented results that contradict this mechanism. Multiple studies found that there was no difference in strength between the late follicular and mid luteal phases [ 21 , 91 , 94 , 99 ], and strength outcomes were lower in the early follicular phase compared to the mid and late luteal phases [ 21 ], increased in the luteal phase [ 89 ], and significantly [ 103 ] and non-significantly [ 99 ] increased in the ovulatory phase.…”
Section: The Impact Of Menstrual Cycle Phase On Objectively Measurmentioning
confidence: 99%